Street Lighting Based on Solar Panels for Night Learning of Santri of Madrasah Aliyah Mambaul 'Ulum - Elfi Yuliza; Riska Ekawita; Lizalidiawati Lizalidiawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The unavailability of adequate street lighting is the main problem in implementing night learning at the Masjid under the Tahfidz program at Madrasah Aliyah Mambaul 'Ulum (MAMU) Bengkulu Tengah. This limitation of street lighting is linked to self-financing and the high cost of supplying electricity from the national electricity company. On the other hand, Bengkulu is located near the equator with renewable energy potential, one of which is solar energy, abundant all day throughout the year. Moreover, technological developments are also impacting the availability of solar panel based solar-to-electricity conversion systems at relatively low costs. The limitation of knowledge and skill in using solar panels as a lighting source is one issue that has yet to utilize the potential of this alternative energy. Therefore, in this community service activity, a series of activities have been carried out to provide solutions to MAMU's lighting problems. The targets of this activity are the students of the Tahfidz program at MAMU. The stages of the activities carried out begin with the preparation in the laboratory, the coordination with the school, the implementation of the community service, the installation of the systems, and the verification of the installed systems. In setting up the service, the activities begin with completing the initial questionnaire, presentations, demonstrations on the use of solar panels, completion of the final questionnaire, questions and answers, door prizes, and group pictures. During the presentation about solar panel technologies, the students showed great enthusiasm. The questionnaire results also showed increased participants' knowledge of the activities. Also, when checking out after the system's installation, the students are satisfied with the solar panel-based lighting that has been installed and promotes learning at night.